ANALISIS TINGKAT KESESUAIAN SOAL GURU MATA PELAJARAN GEOGRAFI BERDASARKAN RANAH KOGNITIF DI SMA NEGERI 2 BANGKINANG KOTA - nidya anggraini hardi; Syafri Anwar (JURUSAN GEOGRAFI FIS UNP, 2023)
Assessment is a process that must be carried out by the teacher to determine the level of achievement of learning materials as well as the ability of students. This study aims to determine the appropriateness of teacher-generated questions based on LOTS, MOTS, and HOTS. This is a descriptiveresearch with a quantitative approach. The object of this research is the final semester exam questions for class X, XI, XII even semesters for the 2020/2021 academic year. The data were collected through survey techniques and using a checklist as an instrument. Based on the research conducted, the following results were obtained: 1). There is a gap in the suitability of the HOTS type questions on the questions made by the Geography subject teacher at SMA N 2 Bangkinang Kota. The gaps in the suitability of the HOTS questions in class X, XI, and XII are 22%, 16%, and 17%, respectively. 2). Obstacles faced by teachers in making questions are a) Teachers do not have documents/guidelines for the distribution of the proportions of questions. b) the teacher's lack of knowledge about the distribution of questions based on LOTS, MOTS and HOTS. Based on the research conducted, it can be concluded that the questions made by the geography subject teacher have a suitability gap on the HOTS type questions. So it is suggested 1.To be able to help achieve learning objectives, the teacher can match the percentage of the distribution of questions. 2. Teachers to be more active in self-development independently. Keywords—quantitative, analysis, suitability, cognitive level